THE DIFFERENCE IN CONSUMER RISK PERCEPTION BETWEENCELEBRITY ENDORSER AND EXPERT ENDORSER IN COLLEGE ADVERTISEMENTS - Euis, Soliha; Naila, Zulfa (Proceeding Fakultas Ekonomi, 2009)
This research aims to examine the difference in consumer risk perception between celebrity and expert endorserin advertisement. We proposed two hypothesis, H1: There is a difference in consumer risk perception between an expertendorser and celebrity endorser in college advertisement. H2: There is a difference in consumer risk perception betweenan expert endorser and a celebrity endorser in college advertisement, which is moderated by the consumer productknowledge.Experimental design was employed in this study with Statistical Experimental- Completely RandomizedDesign. This was conducted on three groups to test H1 and six groups to test H2. To test H1, the participant of eachgroup was given full color print ads using celebrity endorser, expert endorser and nonendorser in advertisement. We gofurther splitting each group with high and low consumer product knowledge to test H2. The participants of thisresearch are 200 students of SMA 7 Semarang.We use One Way Anova to test H1 and two ways Anova to test H2. Our findings showed that there is adifference in consumer risk perception between an expert endorser and celebrity endorser in college advertisement. Wealso found that there is no difference in consumer risk perception between an expert endorser and a celebrityendorser in college’s advertisement, which is moderated by the consumer product knowledge. We also found that thereis difference in consumer’s perceived performance risk, consumer’s perceived financial risk and consumer’ssocial risk between an expert and celebrity endorser in College advertisement. On the other hand, we found there isno difference in consumer perceived psychological risk between an expert and celebrity endorser in College advertisement.Keywords: celebrity endorser, expert endorser, consumer risk perception, consumer product knowledge.